UTILIZATION OF AI TECHNOLOGY TO INCREASE PROFITS IN BUSINESS UNITS MANAGED BY DARUL ANWAR FOUNDATION BANTEN - Napisah, Napisah; Sunarto, Ading; Putri, Aldila Rahma (International Journal of Engagement and Empowerment (IJE2), 2024)
Digital technology plays a vital role in various aspects of human life in the era of digitalization. Electronic devices such as the Internet and phones have changed how we interact, learn, work, and do business. In the current era of computers and the Internet, there are many impacts on society, both positive and negative. Rapid development must be halted in today's technological era. (Amalia et al., 2023). Adaptability is crucial for any country, especially as we enter the 5.0 era or the Super Smart Society. In this concept, modern society is expected to rely on modern technology for daily needs the application of AI evidences this. Artificial Intelligence (AI), a subfield of computer science, enables computers to perform tasks similar to human intelligence (Jaya et al., 2018).  Artificial Intelligence (AI) is a technology that enables computers and machines to simulate human learning, understanding, problem-solving, decision-making, creativity, and autonomy. (IBM.com). AI can analyze large amounts of data quickly and accurately. AI can be used in sales to understand consumer behavior patterns, predict market trends, and optimize budget efficiency. For example, AI can help business units reach the right consumer segments so that the costs incurred in promotions do not exceed the planned budget. AI can also be used to perform several tasks in sales, such as answering customer questions using AI in the form of chatbots, which can improve operational efficiency and budget efficiency. Yayasan Darul Anwar Banten's business unit must still utilize AI technology to develop its business. Many factors, such as a lack of knowledge abouneed for moreicial intelligence, technical expertise, and access to the necessary resources for implementation, can cause this